AN EMPIRICAL ANALYSIS ON THE OPPORTUNITY AND CONSTRAINTS - HARSH BHAI DESAI (International Journal of Multidisciplinary Research and Studies, 2020)
This is due to the fact that the financial resources available at the state level are limited; as a result, it is imperative to guarantee that resources are used effectively. According to this point of view, it is of the highest significance to have an understanding of which factors provide the most significant barriers to the expansion of agricultural production. It has been demonstrated that the several types of vendors operating in the Ranchi market who are in the business of selling veggies are also accountable for a sizeable amount of the price variation in these goods. This inquiry also focuses on the technique of procurement, also known as the supply chain mechanism, of green vegetables by various merchants as well as the costs that are involved with such operations. Despite the fact that prices are fixed on both the farmer's side and the retailer's side, it was discovered that there is a price gap and variations between the two. As a result, in order to determine whether or not there are significant differences between the seasons in terms of the average productivity, cost of production, cost of transportation, and cost of packaging of different vegetables during the pre-monsoon, monsoon, and post-monsoon periods, an analysis of variance with a one-way analysis When manufacturers sell their items to end users or merchants directly rather than going via a middleman, they are able to bring in a higher total net price for their products. Tomatoes were shown to give the best absolute net returns to the farmers, followed by cauliflower, cabbage, brinjal, and local beans across all distribution channels. Cauliflower was found to provide the second highest absolute net returns.